2022
DOI: 10.1371/journal.pone.0273335
|View full text |Cite
|
Sign up to set email alerts
|

Induced resistance to Fusarium wilt of banana caused by Tropical Race 4 in Cavendish cv Grand Naine bananas after challenging with avirulent Fusarium spp.

Abstract: In the last century, Fusarium wilt of banana (FWB) destroyed the banana cultivar Gros Michel. The Cavendish cultivars saved the global banana industry, and currently they dominate global production (~50%) and the export trade (~95%). However, a new strain called Tropical Race 4 (TR4) surfaced in the late 1960’s, spread globally and greatly damages Cavendish plantations as well as manifold local varieties that are primarily grown by small holders. Presently, there is no commercially available replacement for Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…Measures such as quarantine, the destruction of infected plants, and the use of clean planting material are implemented by the governments of LAC member countries, but it is hard to control the spread of the fungus. Research on developing resistant varieties [ 21 ] and improving soil management practices is ongoing [ 22 , 66 , 67 ], but it is uncertain if this will be enough to mitigate the impact of TR4 on the banana industry in the region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures such as quarantine, the destruction of infected plants, and the use of clean planting material are implemented by the governments of LAC member countries, but it is hard to control the spread of the fungus. Research on developing resistant varieties [ 21 ] and improving soil management practices is ongoing [ 22 , 66 , 67 ], but it is uncertain if this will be enough to mitigate the impact of TR4 on the banana industry in the region.…”
Section: Resultsmentioning
confidence: 99%
“…To address the threat of TR4, measures such as quarantine, the destruction of infected plants, and the use of clean planting material were implemented by the governments of Latin American countries. Additionally, research to develop resistant varieties [ 21 ] and improve soil management practices is also ongoing [ 22 ]. Undoubtedly, this disease constitutes a real and particular threat to the livelihoods of small- and medium-sized banana producers in LAC, who mostly lack the economic means to develop measures against yield loss along with the increase in yield production costs [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…malaccensis that lack the TIR motif but has either a CC or no obvious motif at the amino terminus [ 59 , 60 ]. RGA2, which is a CC-NBS-LRR protein, similar to I2 and Fom-2 [ 61 , 62 ], appears to be important in mediating Foc -R1 and Foc -TR4 resistance [ 63 , 64 ]. Furthermore, we have the non-expressor of pathogenesis-related genes 1 (NPR1), which has significant roles in establishing systemic acquired resistance (SAR) and induced systemic resistance (ISR) [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on supporting data showed that RGA2 could be a key factor involved in both R1 and TR4 resistance, whereaas TR4 development depend on activating resistance to Race 1. (García-Bastidas et al, 2022).…”
Section: Fusariummentioning
confidence: 99%